Evaluation of a novel antigen-based rapid detection test for the diagnosis of SARS-CoV-2 in respiratory samples - Porte, Lorena (Int J Infect Dis, 2020)
OBJECTIVES: In the context of the coronavirus disease 2019 (COVID-19) pandemic, the development and validation of rapid and easy-to-perform diagnostic methods are of high priority. This study was performed to evaluate a novel rapid antigen detection test (RDT) for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in respiratory samples. METHODS: The fluorescence immunochromatographic SARS-CoV-2 antigen test (Bioeasy Biotechnology Co., Shenzhen, China) was evaluated using universal transport medium with nasopharyngeal (NP) and oropharyngeal (OP) swabs from suspected COVID-19 cases. Diagnostic accuracy was determined in comparison to SARS-CoV-2 real-time (RT)-PCR. RESULTS: A total of 127 samples were included; 82 were RT-PCR-positive. The median patient age was 38 years, 53.5% were male, and 93.7% were from the first week after symptom onset. Overall sensitivity and specificity were 93.9% (95% confidence interval 86.5–97.4%) and 100% (95% confidence interval 92.1–100%), respectively, with a diagnostic accuracy of 96.1% and Kappa coefficient of 0.9. Sensitivity was significantly higher in samples with high viral loads. CONCLUSIONS: The RDT evaluated in this study showed a high sensitivity and specificity in samples mainly obtained during the first week of symptoms and with high viral loads, despite the use of a non-validated sample material. The assay has the potential to become an important tool for early diagnosis of SARS-CoV-2, particularly in situations with limited access to molecular methods.